Interferon regulatory factor 3 from sea perch (Lateolabrax japonicus) exerts antiviral function against nervous necrosis virus infection. (November 2018) - Zhang, Wanwan; Li, Zelin; Jia, Peng; Liu, Wei; Yi, Meisheng; Jia, Kuntong
Abstract: Interferon (IFN) regulatory factor 3 (IRF3) is a major regulator contributing to the host away from viral infection. Here, an IRF3 gene from sea perch (LjIRF3) was identified and its role in regulating early apoptosis signaling and IFN response was investigated during red spotted grouper nervous necrosis virus (RGNNV) infection. The cDNA of LjIRF3 encoded a putative 465 amino acids protein, containing a DNA binding domain, an IRF association domain and a serine-rich domain. Phylogenetic analysis suggested that LjIRF3 shared the closest genetic relationship with Epinephelus coioides IRF3. LjIRF3 was constitutively expressed in all examined tissues with the highest expression level in the liver. Upon RGNNV infection, mRNA transcript level of LjIRF3 was significantly up-regulated in vivo and in vitro, indicating the involvement of LjIRF3 in immune response to RGNNV infection. Furthermore, overexpression of LjIRF3 significantly suppressed RGNNV replication in vitro, meanwhile significantly up-regulating the expression of IFNI and IFN stimulated genes and resulting in the activation of caspase 3 and 9 proteases in the early stage of RGNNV infection. In short, these results demonstrated that LjIRF3 exerted antiviral function against RGNNV infection via triggering early apoptotic cell death and inducing IRF3-dependent IFN immune response. Highlights: LjIRF3 was significantly up-regulated in response to RGNNV infection in vivo and in vitro . Overexpression of LjIRF3 suppressed RGNNV replication. Overexpression of LjIRF3 triggered early apoptotic cell death during RGNNV infection. Overexpression of LjIRF3 induced the expression of IFN inducible genes.